Pendampingan Penyusunan Proposal Bisnis sebagai Upaya Peningkatan Kapasitas Pengurus Koperasi Desa Merah Putih Kabupaten Bojonegoro - Nanang Setiawan (Fakultas Ekonomi dan Bisnis Islam Universitas Al- Hikmah Indonesia - Jurnal Ekonomi Pengabdian Masyarakat, 2025)
Koperasi Desa Merah Putih (KDMP) is a national strategic program that plays an important role in promoting rural economic self-reliance. As a newly established institution, KDMP management is assisted by a business assistant to enhance managerial capacity, improve the utilization of management information systems, and strengthen the ability to develop feasible and sustainable business plans and proposals. This community service activity focuses on intensive assistance provided by the author as a business assistant for KDMP management in Bojonegoro Regency. The objectives of this program are to support KDMP management in integrating cooperative activities into a management information system, preparing systematic business plans and proposals, and assisting in the implementation of cooperative business operations. The method employed in this activity adopts a mentoring and empowerment approach, implemented through training sessions, consultations, participatory discussions, and hands-on practices tailored to the specific needs of each cooperative. The results indicate an improvement in management’s understanding of information system–based cooperative management, the successful preparation of business plan and proposal documents ready to be submitted to relevant business partners, and enhancements in cooperative governance and operational performance. This program contributes to strengthening the institutional capacity of KDMP and supports the sustainability of village cooperative enterprises in Bojonegoro Regency